Challenges of Arabic Language Education Students in The 4th Semester of STIT Madani Yogyakarta in Learning Arabic Based on The Use of Technology - Mutik Komalasari; Rika Anggraini; Sri Mulyani; Eko Ngabdul Shodikin (PPPBA, 2025)
Digital transformation in education has reshaped the paradigm of Arabic language learning in higher education, particularly for female students who face distinctive challenges in adapting technology to master a linguistically complex language. This study aims to analyze and describe the challenges encountered by fourth-semester female students of the Arabic Language Education Study Program at STIT Madani Yogyakarta in technology-based Arabic learning and the strategies they developed to adapt. Employing a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews, observations, and documentation involving four purposively selected female students. The small sample size was intentionally chosen to allow for an in-depth exploration of individual experiences and contextual nuances, consistent with the phenomenological design. Data were analyzed thematically using Braun and Clarke’s framework, emphasizing credibility, transferability, dependability, and confirmability. The findings reveal three main categories of challenges: technical (device limitations, unstable internet, and limited data), psychological (low motivation, distractions, and language anxiety), and socio-economic (financial constraints and an unconducive learning environment). Despite these barriers, participants demonstrated adaptability through self-regulated strategies, including the use of digital platforms, artificial intelligence (AI) tools, and peer collaboration. The novelty of this research lies in its exploration of female student’ lived experiences in Islamic higher education, integrating gender, socio-cultural, and technological perspectives in Arabic language learning. This study highlights the need for hybrid learning models that combine technology with face-to-face interaction, enhance lecturers’ TPACK competencies, and promote gender-responsive curricula for more inclusive Arabic language education in the digital era.